Piloting Participatory Arts-Based Methods for Exploring Indonesians’ Experiences in a U.S. Biotechnology Training Program - Jamie Loizzo; Richard E Goodman; Mary Garbacz (Journal of Applied Communications, 2018)
Science communication faculty and professionals often train scientists about conveying and delivering critical and sometimes controversial scientific information to public audiences. This qualitative case study was situated in a U.S.-based biotechnology training program funded by the United States Department of Agriculture for connecting Indonesian science fellows with university biotechnology scientists and science communication experts. The researchers piloted a participatory arts-based approach for instructing and researching Indonesian scientists’, professionals’, and educators’ learning and experiences in the program. Participatory and arts-based research has the potential to uncover and bring to light participants’ perceptions. Participants used iPad multimedia kits to demonstrate their learning of the training’s science communication content, co-constructed and conducted interviews, and captured photos and videos chronicling their experiences throughout the program. Results showed participants’ photos predominantly focused on field site and laboratory visits during the training and participants effectively applied digital storytelling techniques presented in the workshops. Themes from the co-constructed interviews included participants’ definitions of biotechnology, concerns about regulation, labeling, and public understanding, and expressing a hope that biotechnology may improve food security in Indonesia. This pilot study has implications for future international science communication training via intentional instructional design and arts-based research for a culture-centered communication approach.
Keywords: biotechnology; arts-based; participatory video; international; training; culture-centered